Music Palace : the power of music seen by visual artists. - Dosogne, Christophe; Ghosn, Joseph; Meddeb, Hind; Thiellement, Pacôme; Wiegersma, Diana (Brussel : Boghossain Foundation, 2014)
Abidin, Adel ; Atay, Fikret ; Avedissian, Chant ; Batniji, Taysir ; Beugnies, Pauline ; Bouabdellah, Zoulikha ; Chahine, Youssef ; Czech, Natalie ; De Jong, Folkert ; Wieder, Ende [e.a.]
Music Palace, Villa Empain, Brussels, 25 september 2014 tot 8 februari 2015
boek